DEVELOPMENT OF LOW-HEAD CROSSFLOW TURBINE PICOHYDRO POWER PLANTS - Gunandi, Gun Gun Ramdlan; Widiawaty , Candra Damis; Subarkah, Rahmat; Abadi, Cecep Slamet; Nufus, Tatun Hayatun; Rizkia , Vika (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
The provision of food, the provision of energy and the provision of information are controlled to improve people's welfare. In 2011, national electricity production by PLN was 11% new and renewable energy. 6% PLTA and 5% PLTP. PLN plans Geothermal Energy to be 13% and Hydro Power Plant still 6%. The availability of PhHPP independently has been developed by many communities. PhHPP with a water wheel drive capacity of around 100 watts, just enough for home lighting. Even though the area's hydro energy potential is quite abundant. The developments that have been carried out have several weaknesses; The PhHPP with a plump turbine type requires a high head, which becomes an obstacle for agricultural irrigation, while PhHPP with a water wheel type has low efficiency. Research was conducted to develop PhHPP with a more efficient low head crossflow turbine type. Development of PhHPP with cross flow turbine type with actual energy potential, head 2 m and flow velocity 1 m/s. Development begins with numerical simulations to optimize the runner width and diameter ratio. Simulation results of the RNG k-ε model for a total inlet pressure of 20114 pascals and an outlet of 0 pascals, the optimum point is at the crossflow turbine runner diameter and turbine width ratio of 0.56.